Sigorta eksperliği ve ekspertiz raporu otomasyonu - Dışpınar, M. Nedret (My University, 2006)
Endüstrileşme ve gelişme çabası içine giren bir ülkenin çözmesi gereken bir çok sorunu vardır. Bu sorunların bir kısmı ülkenin tarihsel gelişiminden kaynaklanırken bir kısmı mevcut teknoloji düzeyine, yönetim biçimine ve eğitim yetersizliğine başlanabilir. Bunların hepsi birlikte sigorta sektöründe bir alt yapı sorunu olarak ele alınan öğelerdir. Her toplumun gösterdiği karakteristik özel problemleri de bulunulabilir. Problemler zaman akışı içinde gerçekleşirken klasik sigortacılık; sigorta endüstrisi haline dönüşürken endüstri toplumunun gereklerine uygun olarak yeni değerler, teknolojiler ve kurumsallaşmalar meydana gelmektedir. Tez çalışmasında görüntü bütünüyle sigorta hasar eksperliği yapı değişikliğinin yansıtılması ve raporlama şekillerinin sigorta eksperliği genel kavramı içinde irdelenmesi yapılmaya çalışılmıştır. Hasar yönetim sistemleri sorunları ve çözümleri üzerinde yapılan araştırma, ekspertiz raporu otomasyonu ile hasar miktarının ve içeriğinin oluşmasında belirgin olan ekspertiz raporlarının bir kesitinin toplumsal değişim mantığı ile incelenerek kamusal ve mesleki alanda düzenleyici olması düşünülmüştür. Sigorta eksperliğinin faaliyet esasları olan sorumluluk, bağımsızlık, mesleki özen ve titizlik, rapor standartları gibi kavramlar baz alınarak ülkemizdeki hasar tespit faaliyetlerinin geliştirilmesi sağlanmaya çalışılmıştır. Eksperlik alanındaki yeterli yasal düzenleme eksikliği, değerleme alanındaki kamusal, mesleki ve

düzenleyici kurum bulunmayışı, branşlar itibariyle eksperlik faaliyetinin ayrı bir uzmanlık gerektirmesi, kaliteli ve kurumsal bir ekspertiz hizmeti gerekliliği gibi haller nedeniyle tezde eksperlerin ana görevleri, şekil ve şartları incelenmiştir. Ayrıca tezde ekspertiz şirketi,eksper,hasar uzmanı gibi temel kavramlar hasar yönetim sistemleri ile birlikte değerlendirilerek birkaç başlık altında sınıflaması yapılmış, Türk sigorta sektöründeki hasar yönetim ve denetim şekilleri araştırılmıştır. Sektördeki hasar sistemleri incelenirken belli dönemdeki uygulamalar ele alınarak hasar maliyetlerini düzenleme şekilleri, hasar denetim biçimleri ve sektörel uygulamalar incelenerek hasar yönetimindeki sorunların çözümüne yönelik çalışmalar yapılmıştır. Gelecekte yapılması gerekli olan yurtdışındaki mesleki ve etik standartların ülkemize adapte edilmesi, standart ve kaliteli ekspertiz hizmeti, rekabeti bozmayan hasar yönetim politikalarının belirlenmesi, lisanlı ve belgeli hasar uzmanı sayısında artış sağlanmasıdır. Buna paralel olarak profesyonelleşme ve kurumsallaşma, faaliyet alanlarının genişlemesi, ekspertiz şirketlerine bilgi ve belge temininde kolaylık sağlayıcı mevzuat düzenlemelerinin yapılması, sektörde işbirliği önemli beklentilerdir. Amaç; eksperlerin sigorta eksperliği mevzuatı uyarınca sağlıklı tetkik yapması için zorunlu olan raporlama işlemlerine ilişkin teknik hizmeti vermek üzere sigorta şirketleri ve sigortalılar tarafından kabul görecek rapor esaslarının, hasar yönetiminin belirlenmesidir. Kasko ve trafik sigortası otomasyon hasar yönetim sistemlerinin analizi ile de araştırmayı tamamlayıcı nitelikte açıklamalara yer verilmektedir ABSRTACT Each country being in an attempt for industrialization and development has countless problems waiting for solution. While some of these resultant problems emerge from the historical development or developmental process, some are ascribable to the existent technological level, polity of that country and lack of education. These are all the factors that need to be evaluated as “infrastructural deficiencies”. There are also some “special to itself” difficulties for each country. Just as the problems come into existence in time and with changing of the traditional selling insurence into an insurence industry, some “newly–arised” norms or practical values that industrial societies commonly required besides some new technological developments and institutionalisations might as well occur. With this evaluation study representing the outcomes of the related research, it was intended to consider the structural changes occurred in the continuum of insurance claim adjusting and to study the appraisal reporting systems within the concept of insurance loss expertising at length. This research referring to the difficulties of loss management system and their solutions, aims to investigate “a constitutive profile of appraisal report automation”, which is underlying the constitution of the appraisal reports for the quantum of damages plus the content of it taking the point in the sense of social change and also to have a regulating or systematizing characteristic within the public sphere. Predicating on such fundamental concepts of insurance damage survey as responsibility, working independence, due professional diligence and rigour, along with the corresponding standards in reporting, our study further intends to achieve the development of the insurance claim adjusting activities. With this research, due to such conditions as the lack of sufficient legal arrangements in insurance survey and that of the government entities, failure of related professional institutions in addition to the absence of regulatory institutions in making appraisals as well as that the business of insurance survey requires a quite different specialization as far as branching is concerned and with a view to the necessity of an institutional survey of high quality, this thesis study tries to be reflecting the basic duties of the experts, the formulation or structure of the business and the requirements of insurance claim adjusting business. Likewise, with the evaluation of loss management systems by a sample study of Turkish Insurance Sector, an additional reference to the issues of expert valuation has also been made besides the concepts of expertising and loss assessment and these are subsumed under such several titles. Pending the survey apropos for the systems of loss management in this sector, after some operational studies relying on different specific applications to have occurred in a certain period of time, various corresponding (operational) studies (i.e. researches) including the solutions of the problems confronted during the loss management were also conducted after researching some “sector-specific” operational practices and claim assessment systems has also been made plus those referring to the analysis and finding of damage costs. “The adaptation process” ensuring the implementation of due professional and ethic standards in our country suggests a “standardized appraisal service of good quality”, defining the loss management policies that do not allow any failure in trade competition in addition to the increase in both licensed (qualified) and authorized experts. Besides professionalism and institutionalization in business; the extension of the scope, making related legislative arrangements, securing necessary information and documents in relation with insurance expertising agents and sectoral collaboration are all marked expectations of prior importance. The main aim of this research is pivoted around the specification of the fundamentals/ basis/ keynotes of the appraisal reports regarding that the experts could achieve to make sound loss assessment with the meaning of the set terms concerning insurance claim adjustment. Availing of the automobile and traffic insurance automation programme and the loss management system analysis, some supplementary explanations are made additionally.
Keywords: Bankalar ve Bankacılık; Sigorta Eksperliği; Sigortacılık